Ligand Influence on Structural Properties and Reactivity of Bis(μ‐oxo)dimanganese(III, IV) Species and Comparison of Reactivity with Terminal MnIV‐oxo Complexes. Issue 47 (18th December 2018) - Lee, Yuri; Jackson, Timothy A.
Abstract: The ligand influence on structure and reactivity of a pair of bis(μ‐oxo)dimanganese(III, IV) complexes was investigated. The pentadentate N4py and DMM N4py ligands were employed to assemble the [Mn III Mn IV (μ‐O)2 (N4py)2 ] 3+ (1 ) and [Mn III Mn IV (μ‐O)2 ( DMM N4py)2 ] 3+ (2 ) species by H2 O2 oxidation of the corresponding Mn II complexes. The electronic absorption and EPR properties of1 and2 are nearly identical. Analysis of the EXAFS region of the Mn K‐edge XAS spectra of1 and2 reveals comparable Mn‐ligand and Mn−Mn distances. Molecular structures of1 and2 from DFT calculations showed only minor variations in Mn‐ligand bond lengths between these complexes. Despite these structural similarities, a ligand influence was observed on the Mn III Mn IV to Mn III Mn III reduction potential. Nonetheless, the oxidation of 2, 4‐di‐ tert ‐butylphenol by1 and2 proceeded at essentially identical rates. In contrast, reactivity comparison between2 and the corresponding monomeric Mn IV ‐oxo species, [Mn IV (O)( DMM N4py)] 2+, showed that the latter complex is a vastly superior oxidant for O−H bond oxidation, showing a rate enhancement of 10 5 at parity of substrate and temperature. Abstract : Ligand influences on the geometric and electronic structure and reactivity of bis(μ‐oxo)dimanganese(III, IV) complexes were investigated. Electronic absorption, EPR, XAS, and DFT calculations reveal strong similarities between two dimanganese(III, IV) complexes, and kinetic studies yielded similar rate constants for phenol oxidation. Reactivity comparison of bis(μ‐oxo)Mn III Mn IV and monomeric Mn IV ‐oxo complexes was performed.